Role of Microbiota and Innate Immunity in Recurrent Clostridium difficile Infection - Stefano Bibbò; Loris Riccardo Lopetuso; Gianluca Ianiro; Teresa Di Rienzo; Antonio Gasbarrini; Giovanni Cammarota (Journal of Immunology Research)
Recurrent Clostridium difficile infection represents a burdensome clinical issue whose epidemiology is increasing worldwide. The pathogenesis is not yet completely known. Recent observations suggest that the alteration of the intestinal microbiota and impaired innate immunity may play a leading role in the development of recurrent infection. Various factors can cause dysbiosis. The causes most involved in the process are antibiotics, NSAIDs, acid suppressing therapies, and age. Gut microbiota impairment can favor Clostridium difficile infection through several mechanisms, such as the alteration of fermentative metabolism (especially SCFAs), the alteration of bile acid metabolism, and the imbalance of antimicrobial substances production. These factors alter the intestinal homeostasis promoting the development of an ecological niche for Clostridium difficile and of the modulation of immune response. Moreover, the intestinal dysbiosis can promote a proinflammatory environment, whereas Clostridium difficile itself modulates the innate immunity through both toxin-dependent and toxin-independent mechanisms. In this narrative review, we discuss how the intestinal microbiota modifications and the modulation of innate immune response can lead to and exacerbate Clostridium difficile infection.